ANALISIS KEJADIAN PENYAKIT GAGAL GINJAL KRONIS PADA PENDERITA DIABETES MELITUS DI INDONESIA : ANALISIS DATA RISET KESEHATAN DASAR 2018 - Rizka, Aldila Selita Lailatul; Kardiwinata, Made Pasek; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT The increasing morbidity rate of Diabetes Mellitus (DM) in Indonesia is estimated that people are not aware of the possible complications that can be suffered. Diabetic Nephropathy (ND) or Chronic Kidney Failure (CKD) is one of the microvascular complications in patients with DM that has affected 3.3% of DM patients in Indonesia. This study aims to determine the incidence of GGK in patients with DM and the relationship between demographic characteristics and behavioral characteristics with the incidence of GGK in patients with DM. This research is a quantitative study with a descriptive cross-sectional design. The study sample of 14,932 was all patients with DM >15 years old in Indonesia who were registered as respondents of Riskesdas 2018. Data were analyzed using the Chi-Square method. It was found that from all samples studied, the incidence rate of GGK in patients with DM was 2%. And the characteristics that have a significant association with the incidence of GGK in patients with DM are gender (OR 1.33; 95%CI 00.0-00.0), physical activity (OR 1.33; 95%CI 00.0-00.0), moderate intensity physical activity (OR = 1.97 95%CI 1.57-2.48) and duration of DM (OR = 1.95 95%CI 1.52-2.49). Further studies are needed regarding the relationship between duration of DM and physical activity with GGK complications. It is also recommended to increase physical activity in patients with DM to avoid worse complications of GGK. Keywords :  Diabetes Mellitus, Chronic Kidney Failure